Evaluation of mechanical stability of nuclear fuel plates under axial flow conditions - Mantecón, Javier González (2019)
Several nuclear research reactors use or are planned with cores containing flat-plate- type fuel elements. The nuclear fuel is contained in parallel plates that are separated by narrow channels through which the fluid flows to remove the heat generated by fission reactions. One of the problems of this fuel element design is the mechanical stability of the fuel plates. High-velocity coolant flowing through the channels can cause large deflections of these plates leading to local overheating, structural failure or plate collapse. As a consequence, the safe operation of the reactor may be affected. In this work, a numerical fluid-structure interaction study was conducted for evaluating the mechanical stability of nuclear fuel plates under axial flow conditions. Five different cases were analyzed. In all cases, the system consisted of two fuel plates bounded by fluid channels but, in case 5, a support comb at the leading edge of the plates was inserted. The pressure loadings caused by the fluid flow were calculated using a Computational Fluid Dynamics model created with ANSYS CFX. The structural response was determined by means of a Finite Element Analysis model generated with ANSYS Mechanical. Both models were coupled using the two-way fluid-structure interaction approach. The results from Case 1 allowed proposing a methodology to predict the critical velocity of the assembly without an inlet support comb. The maximum deflection of the plates was detected at their leading edges. It was detected that, for flow rates in the channels less than a certain value, the maximum deflection increased linearly with the square of the coolant velocity. In contrast, for greater flow rates, a nonlinear behavior was observed. Therefore, that fluid velocity was identified as the critical velocity of the system. Besides, above the critical velocity, an extra deflection peak was observed near the trailing edge of the plates. In cases 2, 3 and 4, the influence of manufacturing deviations and the change of materials properties due to the increment of temperature on the critical velocity was investigated. With these conditions, the critical velocity of the system was found at lower values. Lastly, in Case 5, the effectiveness of using a support comb at the leading edge of the plates was investigated. The results showed that the static divergence at the inlet end is effectively eliminated with the installation of the comb. In addition, the flow-induced deflections along the length of the plates were significantly diminished with the comb.